Using the web 2.0 to enhance the teaching and learning experience in the ESL classroom (Revista Educação, Cultura e Sociedade, 2016)
The use of technology in the classroom setting has been used successfully throughout the years. Plenty of English as Second Language (ESL) students had benefitted from this in order to achieve fluency. Nowadays, ESL instructors are integrating the Web 2.0 in to the classroom setting. According to O’Reilly (2005), this type of technology empowers the end user. Based on this, educators use the Web 2.0 and it’s core based on blogs, wikis and podcasts with plenty of opportunities for the learner. The Web 2.0 offers the learner with a variety of activities that enhance his learning and at the same time motivates him. Power tools are common in the Web 2.0 and enable the learning process because provide alternatives to the ESL learners to work with technology they know. Keywords: Web 2.0; ESL; teaching; learning.